1999
DOI: 10.1177/021849239900700212
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Chest Trauma in a Referral Hospital: A Five-Year Experience

Abstract: From April 1993 to March 1998 patients with chest injuries were retrospectively assessed for the incidence, presentation, and outcome of thoracic trauma. The majority (55.6%) were less than 40 years of age and 83 (92%) were male. The mode and extent of injury, specific intrathoracic organ injuries, associated injuries, flail chest, ventilatory requirements, management, morbidity, and mortality were analyzed. Blunt injuries were seen in 56 (62.2%) and penetrating injuries in 34 (37.7%). Multiple rib fractures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In the present study, out of 100 cases, the maximum cases (42%) of blunt chest injuries were detected in the age group of 21 -30 years and 24% cases were of the age group of 31-40. after that in the age group of 31 -40, 24 cases (24%). Similar finding was observed in the studies conducted by Raju S Iyer 15 , A.L. Ghangale 16 , R.V.…”
Section: The Age Profile Of the Victimssupporting
confidence: 90%
“…In the present study, out of 100 cases, the maximum cases (42%) of blunt chest injuries were detected in the age group of 21 -30 years and 24% cases were of the age group of 31-40. after that in the age group of 31 -40, 24 cases (24%). Similar finding was observed in the studies conducted by Raju S Iyer 15 , A.L. Ghangale 16 , R.V.…”
Section: The Age Profile Of the Victimssupporting
confidence: 90%
“…9,10 This finding on sex distribution, mean age, and age range were in keeping with other findings. 5,8,11 The implication of this is depletion of the productive workforce required even more in developing societies. As authors observed, it is now generally agreed that the majority of chest injured patients (98.2%) require no more than tube thoracostomy for adequate management reserving thoracotomy for those patients with significant hemorrhage or for patients who are hemodynamically unstable, with proven surgical pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…It means among the three pods of life (Tripod), two pods are present in this cavity. [3] The cause responsible for injuries during RTA are usually physical factor like collision between victims and the external environment and acceleration or deceleration forces acting on victim's internal organs.…”
Section: Introductionmentioning
confidence: 99%